Advanced PET imaging in oncology: status and developments with current and future relevance to lung cancer care. Issue 2 (March 2018) - Voigt, Wieland
Abstract : Purpose of review: This review highlights the status and developments of PET imaging in oncology, with particular emphasis on lung cancer. We discuss the significance of PET for diagnosis, staging, decision-making, monitoring of treatment response, and drug development. The PET key advantage, the noninvasive assessment of functional and molecular tumor characteristics including tumor heterogeneity, as well as PET trends relevant to cancer care are exemplified. Recent findings: Advances of PET and radiotracer technology are encouraging for multiple fields of oncological research and clinical application, including in-depth assessment of PET images by texture analysis (radiomics). Whole body PET imaging and novel PET tracers allow assessing characteristics of most types of cancer. However, only few PET tracers in addition to 18 F-fluorodeoxyglucose have sufficiently been validated, approved, and are reimbursed for a limited number of indications. Therefore, validation and standardization of PET parameters including tracer dosage, image acquisition, post processing, and reading are required to expand PET imaging as clinically applicable approach. Summary: Considering the potential of PET imaging for precision medicine and drug development in lung and other types of cancer, increasing efforts are warranted to standardize PET technology and to provide evidence for PET imaging as a guiding biomarker in nearly all areas of cancer treatment.